Overview of Approaches on Sustainable Development Management - Tuyet, Dang Thi Anh; Quyen, Hoang Thi (VNU Journal of Science: Policy and Management Studies; Vol 36 No 4DO - 10.25073/2588-1116/vnupam.4258, 2020)
So far, as people become more and more aware of the meaning and importance of the natural and social environment, the concept of "sustainable development" is also constantly being expanded. Researchers around the world have spent a lot of time on developing perspectives on "sustainable development" and "sustainable development management". Our main contribution in this paper is to explore and analyze approaches for sustainable development management in order to find the key components for building a sustainable development management system that is appropriate for Vietnam's practices in a new context.